A review of commonality models in manufacturing resources planning: state-of-the-art and future directions - Wazed, M.A.; Ahmed, S.; Bin Yusoff, N. (2008)
Purpose - The main purposes of this paper are to enhance the understanding of commonality models in manufacturing resource planning by documenting the current state of affairs, and to stimulate fruitful future research by identifying gaps between the relevant issues and available academic literature. Design/methodology/approach - This paper is based on a comprehensive review of the articles from authentic publications on resources commonality for the various product mixes and the pertinent models. The papers are analyzed to identify the current scenarios and draw future research directions in the area. Findings – In real world manufacturing settings, parts commonalities occur in their own ways or can be planned for their preferred occurrences. The use of common components for different products in a company is important for managing product variety and maintaining competitiveness in this age of mass customization and supply chain struggle. The paper finds that development of mathematical model to study the effects of commonality in the multi-stage systems with multiple products and multiple common items are remain in the virgin area of research. Effects of uncertainty factors on the models are other issues not yet covered in literatures. Experiments and empirical studies in this fissure also needed further attention. Originality/value – The contribution of this paper is to provide a summary of the current state of affairs in component commonality and its models, and to point out the future research directions. A review of the work in this expanding and complex area of demand has been provided that identify the issues in this area. This is a comprehensive and up-to-date review of literatures on component commonality in manufacturing resource planning.